Rescue Strategy in a Termite: Workers Exposed to a Fungal Pathogen Are Reintegrated Into the Colony - Moran, Megan N.; Aguero, Carlos M.; Eyer, Pierre-André; Vargo, Edward L. (Frontiers in Ecology and Evolution, 2022)
Social insect colonies are characterized by an efficient division of labor, allowing high-value individuals (i.e. reproductives and brood) to be sheltered from tasks associated with increased risk of pathogen exposure, such as foraging or corpse disposal. This social organization helps limit the transmission of disease throughout the colony. Further, individuals can actively respond to imminent disease threats by altering their behaviors as a means of social immunity. In subterranean termites, although workers typically avoid detected pathogens, they can be attracted to pathogen cues when a nestmate is infected. Infected termites are usually groomed, but they may instead be cannibalized if the infection has already become lethal. The mechanisms governing these changes in behavior are unclear. We set out to examine immediate changes in individual behaviors, investigating the role that the infected individual plays in communicating its infection status to nestmates. We also assessed gradual changes in social organization after the re-introduction of an infected termite to the colony. Our results reveal that infected termites likely do not signal their infection status to nestmates through shaking behaviors and reduced movements, suggesting the occurrence of other mechanisms used in communicating infection. We also found that infected termites do not self-isolate and may travel to the densest part of the colony, where they can potentially benefit from grooming by large groups of nestmates. These results provide new insights into how individual changes in immune behaviors contribute to overall colony health, highlighting that, at early stages of infection, termites favor a rescuing strategy rather than isolation and/or cannibalism.